Redirected Primary Human Chimeric Antigen Receptor Natural Killer Cells As an “Off-the-Shelf Immunotherapy” for Improvement in Cancer Treatment - Oberschmidt, Olaf; Kloess, Stephan; Koehl, Ulrike (Frontiers in Immunology, 2017)
Primary human natural killer (NK) cells recognize and subsequently eliminate virus infected cells, tumor cells, or other aberranT-cells. However, cancer cells are able to develop tumor immune escape mechanisms to undermine this immune control. To overcome this obstacle, NK cells can be genetically modified to express chimeric antigen receptors (CARs) in order to improve specific recognition of cancer surface markers (e. g. CD19, CD20, ErbB2). After target recognition, intracellular CAR domain signaling (CD3zeta, CD28, 4-1BB, 2B4) lead to activation of PI3K or DNAX proteins (DAP10, DAP12) and finally to enhanced cytotoxicity, proliferation, and/or IFNgamma release. This mini-review summarizes both the first pre-clinical trials with CAR engineered primary human NK cells and the translational implications for “off-the-shelf-immunotherapy” in cancer treatment. Signal transduction in NK cells as well as optimization of CAR signaling will be described, becoming more and more a focal point of interest in addition to redirected T-cells. Finally, strategies to overcome off-target effects will be discussed in order to improve future clinical trials and to avoid attacking healthy tissues.